2009
DOI: 10.4067/s0718-58392009000300020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Culture Medium in Callogenesis from Adult Walnut Leaves (Juglans regia L.)

Abstract: To define preliminary aspects of walnut (Juglans regia L.) callogenesis in indirect propagation systems, this work analyzed callogenic induction in adult leaves of walnut in broadleaf trees (BTM), Murashige and Skoog (MS) Driver Kuniyuki Walnut (DKW) and Woody Plant (WPM) media. Leaf segments of 1 cm 2 , previously sterilized, were placed in each culture medium, supplemented with 21.4 µM naphtalene acetic acid (NAA) and 8.8 µM 6-benzylaminopurine (BAP). A completely random design was used; the experimental uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 34 publications
0
7
0
3
Order By: Relevance
“…Those nutrients are likely to be the factor which influence the responses of explants towards the formation of callus (Osman et al, 2016). In the present study, the effects of using WPM medium, in bay leaf tree (Cinnamomum tamala) by Sharma and Nautiyal (2009) reported that almost all explants and plant growth regulator treatments produced compact callus and also by Avil´es et al (2009) in Juglans regia L even in endosperm explant of Barringtonia racemosa L by Osman et al (2016) Non embryogenic callus generally has lost regeneration capacity. But the present investigation reveals that non embryogenic callus can be turned into embryos and plantlets if cultured on appropriate medium.…”
Section: Discussionmentioning
confidence: 53%
“…Those nutrients are likely to be the factor which influence the responses of explants towards the formation of callus (Osman et al, 2016). In the present study, the effects of using WPM medium, in bay leaf tree (Cinnamomum tamala) by Sharma and Nautiyal (2009) reported that almost all explants and plant growth regulator treatments produced compact callus and also by Avil´es et al (2009) in Juglans regia L even in endosperm explant of Barringtonia racemosa L by Osman et al (2016) Non embryogenic callus generally has lost regeneration capacity. But the present investigation reveals that non embryogenic callus can be turned into embryos and plantlets if cultured on appropriate medium.…”
Section: Discussionmentioning
confidence: 53%
“…Baillon y Castanea sativa Mill. (Ríos et al 2005, Avilés et al 2009, Latsague et al 2009. No obstante, cabe destacar que los altos niveles de supervivencia obtenidos pueden ser un indicador de la calidad inicial de los microtallos utilizados en este ensayo, ya que es importante considerar que, además de los contenidos hormonales, las características anatómicas y fisiológicas de las plantas micropropagadas se hacen necesarias para su supervivencia tanto en condiciones in vitro como ex vitro (Hartmann et al 2002, Ríos et al 2005.…”
Section: Discussionunclassified
“…Micropropagation can be used for large-scale multiplication of cultivars with desirable traits and the production of healthy and disease-free plants. The micropropagation of J. regia is possible via the cultivation of nodal segments, cotyledon, immature cotyledons, ovules, mature embryos and meristems (Aly et al, 1992;Pijut, 1993a, b;Long et al, 1995;Vahdati et al, 2004;Avıĺes et al, 2009). Progress in developing methods for micro-propagation of J. regia has been very successful over the past decade.…”
Section: Micropropagation Of Walnutmentioning
confidence: 99%